Studies in the philosophy of science - Rescher, Nicholas (Nicholas Rescher collected papers, 2006)
Since Rescher's earliest publication of the middle 1950's in this field, the philosophy of science has constituted one focus of his interest and preoccupation. Some dozen of Rescher's contributions to the field are published in the present volume, and they combine to convey his favored way of blending empirical data with philosophical theorizing.